2020
DOI: 10.1186/s12979-020-00192-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 disease severity and diabetes: why the connection and what is to be done?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel virus responsible for the current coronavirus disease 2019 (COVID-19) pandemic, has infected over 3.5 million people all over the world since the first case was reported from Wuhan, China 5 months ago. As more epidemiological data regarding COVID-19 patients is acquired, factors that increase the severity of the infection are being identified and reported. One of the most consistent comorbidities associated with worse outcome in COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 87 publications
4
51
0
1
Order By: Relevance
“…For example, a recent modeling study estimated that 20% of those aged 70 years or older patients with COIVD-19 were severe requiring hospitalization whereas only <1% of those younger than 20 years needed so [23], while a Korean study reported that the age-specific death rate was the highest among patients over 70 years of age, with underlying diseases in their circulatory system [27]. Older individuals with diabetes mellitus and an acute respiratory illness are usually susceptible to develop complications such as severe acute respiratory syndrome (SARS), Middle East Respiratory Syndrome (MERS), influenza (including COVID-19), and thus, to be at higher risk of mortality [10]. Furthermore, it has been suggested that diabetic COVID-19 patients are more susceptible to an 'inflammatory storm', which is associated with rapid deterioration and high mortality risk [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent modeling study estimated that 20% of those aged 70 years or older patients with COIVD-19 were severe requiring hospitalization whereas only <1% of those younger than 20 years needed so [23], while a Korean study reported that the age-specific death rate was the highest among patients over 70 years of age, with underlying diseases in their circulatory system [27]. Older individuals with diabetes mellitus and an acute respiratory illness are usually susceptible to develop complications such as severe acute respiratory syndrome (SARS), Middle East Respiratory Syndrome (MERS), influenza (including COVID-19), and thus, to be at higher risk of mortality [10]. Furthermore, it has been suggested that diabetic COVID-19 patients are more susceptible to an 'inflammatory storm', which is associated with rapid deterioration and high mortality risk [18].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid conditions such as diabetes mellitus, respiratory, cardiovascular and renal illnesses, and obesity, and an older age group are known to be positively associated with poor outcomes among COVID-19 patients [10][11][12][13]. Furthermore, research studies have demonstrated that COVID-19 patients with diabetes have poorer clinical prognoses, are at higher risks of complications, such as respiratory failure and acute cardiac injury, and have shorter overall survival times than their non-diabetic counterparts [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, diabetes mellitus reportedly correlates with the severity of COVID-19 and associated mortality, but no increase in susceptibility to SARS-CoV-2 infection have been reported to date[23].The serological assessment confirmed infection in most individuals who reported positive testing for SARS-CoV-2 by PCR. However, repeated testing over >4 weeks with at least two separate assays each did not detect antibodies in six individuals (two with positive in-house PCR results and four with reported positive external PCR results)(S8 Fig,No.…”
mentioning
confidence: 68%
“…Current statistics show a correlation of COVID-19 with gender [123] [124], and age [125] of infected patients. Comorbidities, such as hypertension [126], diabetes [127], cardiovascular disease [128], asthma, chronic obstructive pulmonary disease (COPD) [129] can lead to serious difficulties. Triggering of comorbidities was also detected in SARS-CoV-1 infection in patients who did not have such damage before [130].…”
Section: Challenges Of the Physiologic Regulation And Controlmentioning
confidence: 99%